THE INFLUENCE OF LONG-TERM TREATMENT WITH CARVEDILOL ON LIFE QUALITY IN CHRONIC HEART FAILURE, AS ASSESSED BY A DOUBLE BLIND PLACEBO-CONTROLLED STUDY - A. A. Upnitsky; A. A. Manoshkina; N. A. Korableva; Y. B. Belousov (Российский кардиологический журнал)
The influence of long-term treatment with Carvedilol on life quality in chronic heart failure, as assessed by a double blind placebo-controlled study.